Water Quality Management Select Proceedings of ICWEES-2016 (Water Science and Technology Library,, 2018)
This book comprises two parts. The first part deals with some aspects of wastewater treatment, encompassing various types of technologies for treating wastewater and evaluation. The technologies, biochemical as well as chemical, including evaluation of technologies are also discussed. Part 2 is on solid waste management. It includes both municipal and industrial waste management. The book is of interest to researchers and practitioners in the field of water resources, hydrology, environmental resources, agricultural engineering, watershed management, earth sciences, as well as those engaged in natural resources planning and management. Graduate students and those wishing to conduct further research in water and environment and their development and management find the book to be of value.